2011
DOI: 10.1182/blood-2010-07-294447
|View full text |Cite
|
Sign up to set email alerts
|

Thrombospondin-1 is not the major activator of TGF-β1 in thrombopoietin-induced myelofibrosis

Abstract: Transforming growth factor-␤1 (TGF-␤1) is the most important cytokine involved in the promotion of myelofibrosis. Mechanisms leading to its local activation in the bone marrow environment remain unclear. As a recent study has highlighted the role of thrombospondin-1 (TSP-1) in platelet-derived TGF-␤1 activation, we investigated the role of TSP-1 in the TPO high murine model of myelofibrosis. Two groups of engrafted mice, WT TPO high and Tsp-1-null TPO high , were constituted. All mice developed a similar myelo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 24 publications
(25 reference statements)
0
14
0
Order By: Relevance
“…Our finding is consistent with recent observations where the absence of TSP-1 does not confer protection in models of fibrosis in which TGF-β1 is thought to be causally involved. 15,16 In both models, increased fibrosis was observed in the absence of TSP-1. 15,16 …”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Our finding is consistent with recent observations where the absence of TSP-1 does not confer protection in models of fibrosis in which TGF-β1 is thought to be causally involved. 15,16 In both models, increased fibrosis was observed in the absence of TSP-1. 15,16 …”
Section: Discussionmentioning
confidence: 93%
“…14 It has been suggested that the impaired lung homeostasis in thbs1 −/− mice is due to a failure to activate latent TGF-β1 10,14 and, therefore, predisposing the mice to impaired tissue repair and unresolved inflammation. However, recent studies have shown that TSP-1 is not required for the activation of TGF-βl in vivo and thbs1 −/− mice are not protected from developing either pulmonary fibrosis or myelofibrosis, 15,16 both disease processes in which TGF-β1 has been implicated as a central regulator. Here, we present an alternative mechanism by which thbs1 −/− mice show impaired lung homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…19 Some of these proteins, such as thrombospondin-1 and osteopontin, whose role in the pathogenesis of myelofibrotic myeloid neoplasms has been postulated, share with SPARC detrimental effects on the BM stroma homeostasis related to their up-or down-regulation in hematologic malignancies. [51][52][53][54] Merging together our results from in situ expression analyses on human myeloid neoplasms and in vivo mouse models, we could hypothesize that the BM stroma response to myeloproliferative stimuli is entwined with the status of stromal SPARC expression. Increased or defective expression of SPARC in the BM stroma may exert different, yet detrimental, effects by fostering the development of fibrotic changes or inducing a flawed stromal niche permissive for the deregulated myeloid expansion, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…To become functionally active, TGF-b needs to be activated from its latent state into a biologically active cytokine; such activation may occur through a spectrum of molecular processes, among which activation by aV-containing integrins plays the most important role, making them an ideal target for innovative antifibrotic therapies [108,109]. Thrombospondin is also an important activator of latent TGF-b [110,111], but is not required in all cases of tissue fibrosis, including in lung [112,113].…”
Section: Tgf-bmentioning
confidence: 98%